The use of sodium hypochlorite in the post-harvest handling of fresh cauliflower (Brassicea var. Botrytes) - Llamas, Miciela F.; Azanza, Ma. Patricia V. (1997.)
The use of sodium hypochlorite wash in teh postharvest handling of fresh cauliflowers was studied. The effectivity of varying concentrations of sodium hypochlorite (200 and 250 mg/L) at varying contact time (20, 30 and 40 seconds) were evaluated through objective tests including microbiological and physico-chemical analyses from 0, 3, 8, 14 and 20 days at refrigerated storage. In Phase 1, the total aerobic microorganisms of cauliflowers were initially about 5.73 to 6.51 log10 CFU/g on untreated cauliflowers and increased to 7.09 log10 CFU/g by the 20th day of storage. Treatment with 200 and 250 mg/L or 20 seconds significantly reduced the growth of microorganisms, but the 200 mg/L concentration of NaOCl was found to have more effective antibacterial action than 250 mg/L concentration. Based on the study, the effectiveness of the chlorine solution used varied with pH. The chlorine solution with the higher concentration has a correspondingly high pH and it i less effective against spoilage microorganisms. Total aerobic counts on 200 mg/L-treated cauliflowers were initially 4.24 log10 CFU/g and slowly grew to 5.88 log10 CFU/g by the 20th day of storage. The yeast and mold counts for the 200 mg/L treatment showed a general increase from 3.05 to 3.70 log10 CFU/g for the first 8 days, then decreased gradually to 1.92 log10 on the 20th day. The introduction of chlorine in fresh cauliflower slightly influenced the pH of the samples. There was no significant difference in pH values observed for all the treated and untreated samples. Chlorine treatment of cauliflower exhibited little effect in terms of hue, value and chroma of all cauliflower samples during refrigerate storage. Texture values indicate that chlorine treatment had significantly helped in preserving the textural quality of the curd. In Phase 2, prolonging the treatment with sodium hypochlorite by increasing the contact time also significantly reduced the growth of microorganisms in the cauliflowers. Mist-spray-experiment with 200 mg/L sodium hypochlorite for 30 seconds was found to be most effective in reducing the aerobic populations approximately 100-fold. The results of pH, color and texture determinations indicate that the varying contact time of chlorine treatment used are not significantly different. From this study, treatment with 200 mg/L sodium hypochlorite for 30 seconds is the recommended concentration and contact time which can be used to reduce spoilage microorganisms in cauliflowers. Since the bactericidal effectiveness of chlorine depends largely upon the pH of the solution, the pH of the sodium hypochlorite to be used should be in the practical range of 6.5 to 7.5 in order to reduce microbial population by approximately 99.9%.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Sodium hypochlorite; Vegetables -- Postharvest handling